ESTHER ALLEN E SUSAN BERNOFKSY, «IN TRANSLATION: TRANSLATORS ON THEIR WORK AND WHAT IT MEANS», COLUMBIA UNIVERSITY PRESS, 2013, 254 PÁGS. - Tallone, Laura (POLISSEMA – Revista de Letras do ISCAP, 2019)
.